Literature Review: Pengaruh Senam Rheumatik terhadap Penurunan Nyeri dan Kekakuan Sendi pada Lansia dengan Rheumatoid Arthritis di Komunitas - Rossa Selina; Bilqis Azzahro; Dita Nurlatifah; Selvyana Putri; Kristia Sukma Sari; Fandu Fauzan Suntana; Lilis Lismayanti (CV. ALIM'SPUBLISHING, 2026)
Rheumatoid Arthritis is a chronic autoimmune disease affecting the joints and has become a major health concern among the elderly, characterized by pain, stiffness, swelling, and reduced functional ability that significantly impacts quality of life. Although systematic evidence remains limited, non-pharmacological treatment such as rheumatic gymnastics is considered safe, affordable, and independently applicable by elderly individuals in the community. This study aims to analyze the effect of rheumatic gymnastics on reducing joint pain and stiffness in elderly patients with Rheumatoid Arthritis in the community. A descriptive literature review method was employed following the PRISMA framework through searches on Google Scholar and SciSpace databases covering publications from 2021 to 2026, with seven articles meeting the inclusion criteria and analyzed narratively. The synthesis results consistently demonstrated significant reductions in pain scales following rheumatic gymnastics interventions across all included studies, with significance. Intervention protocols with a frequency of three to seven sessions per week and a duration of 15–30 minutes per session proved most effective. Improvements in joint stiffness were also reported through increased flexibility and range of joint motion. Rheumatic gymnastics is recommended to be integrated into community-based elderly health programs as an evidence-based, safe, effective, and sustainable non-pharmacological intervention. Rheumatoid Arthritis adalah penyakit autoimun kronis yang menyerang persendian dan menjadi masalah kesehatan utama bagi orang tua. Ini ditandai dengan nyeri, kekakuan, pembengkakan, dan penurunan kemampuan fungsional, yang sangat mempengaruhi kualitas hidup. Meskipun penelitian mendalam belum dilakukan tentang pengobatan nonfarmakologis, seperti senam rematik, yang dianggap aman, murah, dan dapat dilakukan secara mandiri oleh orang tua di masyarakat. Tujuan dari penelitian ini adalah untuk melihat bagaimana senam rematik berdampak pada penurunan nyeri dan kekakuan sendi pada orang tua yang menderita RA di komunitas. Metode yang digunakan adalah literature review deskriptif menggunakan panduan PRISMA melalui penelusuran Google Scholar dan SciSpace rentang tahun 2021–2026, dengan tujuh artikel yang memenuhi kriteria inklusi dan dianalisis secara naratif. Hasil sintesis menunjukkan seluruh studi secara konsisten melaporkan penurunan skala nyeri bermakna setelah intervensi senam rematik, dengan nilai signifikansi. Protokol dengan frekuensi tiga hingga tujuh kali per minggu dan durasi 15–30 menit per sesi terbukti paling efektif. Perbaikan kekakuan sendi juga dilaporkan melalui peningkatan fleksibilitas dan lingkup gerak sendi. Senam rematik direkomendasikan diintegrasikan ke dalam program komunitas sebagai intervensi nonfarmakologis berbasis bukti yang efektif, aman, dan berkelanjutan.